2009
DOI: 10.1111/j.1439-0434.2009.01576.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Magnaporthe grisea to the Sterol Demethylation Inhibitor Fungicide Propiconazole

Abstract: Baseline sensitivity of Magnaporthe grisea to a sterol demethylation inhibitor (DMI) propiconazole was determined using 52 wild-type single-spore isolates. The 50% effective concentrations of these 52 isolates to propiconazole ranged from 0.145 to 1.446 lg ⁄ ml. Among the 52 isolates, two (07-82 and 04-006) were hypersensitive to propiconazole. The propiconazolehypersensitive (PHS) isolates were also hypersensitive to another DMI fungicide triadimefon, but not to a benzimidazole fungicide carbendazim. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…These fungicide concentrations were selected based on a preliminary experiment that established a dose-response curve using 16 isolates of PoTl and 12 doses of each fungicide. Because we could not find a sensitive strain within the PoTl populations, we included seven rice blast strains (PoOl), which belong to the same phylogenetic species as PoTl, have very similar CYP51A and CYP51B target genes, have no apparent differences in baseline sensitivity to DMIs, and were found to be highly sensitive to azoles (Fang et al, 2009;Pak et al, 2016;Ceresini et al, 2018;Dorigan et al, 2019 ( Figure S2). PCR was performed with Phusion High-Fidelity DNA polymerase (New England Biolabs), according to the manufacturer's instructions, with an annealing temperature of 70°C and an extension time of 60 s. Products were purified using the Wizard SV Gel and PCR Clean-Up System (Promega), then Sanger-sequenced by Eurofins Genomics (Germany) using sequencing primers CYP51B_912F, CYP51B_2704R, and CYP51B_1556F ( Figure S2).…”
Section: Measuring Sensitivity To Tebuconazole and Epoxiconazolementioning
confidence: 99%
“…These fungicide concentrations were selected based on a preliminary experiment that established a dose-response curve using 16 isolates of PoTl and 12 doses of each fungicide. Because we could not find a sensitive strain within the PoTl populations, we included seven rice blast strains (PoOl), which belong to the same phylogenetic species as PoTl, have very similar CYP51A and CYP51B target genes, have no apparent differences in baseline sensitivity to DMIs, and were found to be highly sensitive to azoles (Fang et al, 2009;Pak et al, 2016;Ceresini et al, 2018;Dorigan et al, 2019 ( Figure S2). PCR was performed with Phusion High-Fidelity DNA polymerase (New England Biolabs), according to the manufacturer's instructions, with an annealing temperature of 70°C and an extension time of 60 s. Products were purified using the Wizard SV Gel and PCR Clean-Up System (Promega), then Sanger-sequenced by Eurofins Genomics (Germany) using sequencing primers CYP51B_912F, CYP51B_2704R, and CYP51B_1556F ( Figure S2).…”
Section: Measuring Sensitivity To Tebuconazole and Epoxiconazolementioning
confidence: 99%
“…DMI fungicides are the largest group of antifungal compounds that are widely used in modern agriculture and have been utilized in the control of plant diseases caused by Ascomycetes , Basidiomycetes and Fungi imperfecti. Epoxiconazole and propiconazole, belonging to the DMI fungicide group, have been reported to effectively control rice blast [ 36 , 37 , 38 ]. Metconazole is a DMI fungicide, and previous studies have shown that this fungicide has strong inhibitory effects on the mycelial growth of F. graminearum and F. pseudograminearum [ 30 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2015) analyzed the effect of azoxystrobin and kresoxim-methyl fungicides for blast control in irrigated rice in China and found that both fungicides had disease control superior to 73% of efficiency and resulted in high grain yield, these results are in contrast of our results. Others reports showed that fungicide azoxystrobin is efficient in the rice blast control with direct reflection on grain yield in countries such as Italy, Taiwan, and the United States (Chen et al, 2015;Kunova et al, 2014;Kunova et al, 2012;Jin et al, 2009;Fang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%